Celiac Plexus Neurolysis for Abdominal Cancer Pain: A Systematic Review. Issue 8 (26th June 2013) - Nagels, Werner; Pease, Nikki; Bekkering, Geertruida; Cools, Filip; Dobbels, Patrick
Abstract Objective This systematic review assesses the effectiveness and side effects of celiac plexus neurolysis (CPN) in the treatment of upper abdominal cancer pain, and evaluates whether there are any differences between the percutaneous and endoscopic ultrasound‐guided (EUS) denervation techniques. Methods Five databases were searched, expanded by assessing the reference lists of all retrieved papers. Sixty‐six publications fulfilled the inclusion/exclusion criteria and were included in the systematic review. Randomized controlled trials were available for the percutaneous CPN, and therefore meta‐analyses were performed for pain, opioid consumption, and specific side effects. The quality of life data were too heterogeneous to be assessed by a meta‐analysis, and evidence for EUS CPN could only be evaluated by observational studies. Results Meta‐analyses show that percutaneous CPN significantly improves pain in patients with upper abdominal cancer, with a decrease in opioid consumption and side effects. It is unclear whether there is any change in quality of life. Case series suggest that EUS CPN improves pain. No conclusion can be made about EUS CPN's influence on opioid consumption. Although CPN is a safe procedure, side effects and complications can occur with both the percutaneous and EUS techniques. Conclusions Following this review, evidence suggests that CPN should be considered in patients with upper abdominal cancer where the pain is not adequately controlled with systemic analgesics or when significant opioid‐induced side effects are present. The percutaneous approach remains the standard technique as robust evidence for EUS CPN is lacking.